Integrating Business Values the Legality, Morality, and Social Responsibility of Motorola (2019)
This paper examines how Motorola, Inc. integrates its business values (legal values, moral values, and social responsibility) in order to maintain its respectable position in the market and in the society. Motorola's legal values go beyond the requirements of the Telecommunications Deregulation Act of 1996; their moral values are established by following a strict business code or corporate governance act that foresees their interest in being respectful of all society rules; and their social responsibility goes beyond simple community-approach programs into great contributions to education, science, and technology. After the business values review, it is required to recall the importance for Motorola in this era of rapid changes and increased competition, to continue to strike the right balance of abiding by the law; and being morally and socially responsible, while still seeking a competitive edge and making a profit for its stakeholders.